Pendalaman Materi Bunyi dan Cahaya: Studi Kasus Penerapan Bunyi dan Cahaya Dalam Kehidupan Sehari-hari - Riznaini Ika Utami; Fingka Wahyu Anggraini; Sulis Wahyu Ningsi; Divanny Aulia Hanif; Wahyu Kurniawati (International Forum of Researchers and Lecturers, 2024)
This research aims to find out about sound and light materials. Researchers use qualitative research and this type of research is a descriptive method that groups people, an object, a condition, and an event. The descriptive method is a method that describes or analyzes a problem. Qualitative research is divided into 2, namely primary data through interviews and documentation, while secondary data through the books studied. The aim of this research is to analyze sound and light material which includes its properties and application in life. daily. The results of this research show that sound is a vibration that propagates as a wave through solid, liquid or gas media and sound is also defined as a series of waves of changes in density and sound pressure, while light is a wave that passes through a vacuum.